2021
DOI: 10.1101/2021.05.25.445690
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Salmonella Typhimurium uses anaerobic respiration to overcome propionate-mediated colonization resistance

Abstract: The gut microbiota benefits the host by limiting enteric pathogen expansion (colonization resistance) partially via the production of inhibitory metabolites. Propionate, a short-chain fatty acid produced by microbiota members, is proposed to mediate colonization resistance against Salmonella enterica serovar Typhimurium (S. Tm). Here, we show that S. Tm overcomes the inhibitory effects of propionate by using it as a carbon source for anaerobic respiration. We determined that propionate metabolism provides an i… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…The use of tetrathionate and nitrate as terminal electron acceptors allows Salmonella to use poorly fermentable carbon sources such as ethanolamine derived from enterocytes membrane; fructose‐asparagine derived from host diet; and 1,2‐propanediol, succinate, and propionate that are by‐products of microbial fermentation [17,19,93–95]. The exploitation of these carbon sources ensures a growth advantage over commensal bacteria, which solely rely on fermentation for growth [17,19,93–95].…”
Section: Inflammation and The Newly Created Nichementioning
confidence: 99%
“…The use of tetrathionate and nitrate as terminal electron acceptors allows Salmonella to use poorly fermentable carbon sources such as ethanolamine derived from enterocytes membrane; fructose‐asparagine derived from host diet; and 1,2‐propanediol, succinate, and propionate that are by‐products of microbial fermentation [17,19,93–95]. The exploitation of these carbon sources ensures a growth advantage over commensal bacteria, which solely rely on fermentation for growth [17,19,93–95].…”
Section: Inflammation and The Newly Created Nichementioning
confidence: 99%
“…Earlier work showed that Salmonella induced inflammation created reactive oxygen and nitrogen species in the luminal environment, increasing the availability of oxygen and potentiating formation of tetrathionate and nitrate [9]. Increased concentrations of these terminal electron acceptors allowed Salmonella to respire and out-compete obligate fermentative commensals like members of the Clostridia [6,10]. Additionally, in the remodeled gut ecosystem respiring Salmonella benefited from unique access to non-competitive carbon sources like propionate and ethanolamine [11,12].…”
Section: Introductionmentioning
confidence: 99%